ANALYSIS OF CONNOTATIVE MEANINGS IN THE SONGS ON THE KONSPIRASI ALAM SEMESTA ALBUM BY FIERSA BESARI - Andin Primadani Putri; Syifa Fauziah Azhaar; Aveny Septi Astriani (Journal of Language and Literature, 2022)
Language is the most important communication tool in human life. Every language spoken by a human being has a meaning to be conveyed to its listeners. How to communicate is not only through a conversation, but can be through other media, one of which is with music or songs. Connotative meaning is present when someone wants to convey a language in a subtle way, without having to clearly talk about what you want to convey. The purpose of this study was conducted to find out the connotative meaning, not only in a conversation, but also in song lyrics. Song lyrics are one of the media that is widely used in expressing a feeling or thing to say, without having to say it directly. This research uses a qualitative descriptive method, which can be used in analyzing a connotative meaning in a song lyric. Fiersa Besari has an album entitled Konspirasi Alam Semesta. The story described in the album can be proven by the 14 song lyrics which are related and have connotative meanings. The title of the first song is entitled Konspirasi Alam Semesta, with song lyrics that describe a meeting. In the sentence Kepakkan sayapmu bawa aku terbang then in the sentence Pernahkah kau terjatuh secara sukarela? then in the sentence Cara mengeja rasa tak bernama, seketika itu pula jagat raya berhenti bergerak, jiwamu terbakar, ragamu lebur. The lyrics of the song have the meaning of someone who has feelings for someone of the opposite sex.